Evidence-based management of diabetes - Vora, Jiten; Buse, John B. (Tfm Pub., 2012)
Addresses many of the most pertinent issues concerning delivery of diabetes care such as: Is diabetes preventable in high-risk individuals? What is the role of treating glycaemia in reducing macrovascular disease? Who and how to treat hyperglycaemia in acute coronary syndromes? Has there been any progress in the management of gestational diabetes?